Dental Caries Experience and Molar-incisor Hypomineralisation in Children - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:While efforts have been directed at reducing caries prevalence and its consequences by increasing access to fluoride in developed countries, its prevalence in developing countries is still on the increase. This study determined caries experience, pattern and severity in children with and without molar-incisor hypomineralisation (MIH).Materials and Methods:This was a cross-sectional, hospital-based study in children aged 3–16 years whose parents/legal guardians consented to participate in the study. They were recruited when they presented at the Paediatric dental clinic in a tertiary institution in Nigeria where assessments of their caries status (using the Decayed, Missing and Filled Teeth/decayed, missing and filled teeth [DMFT/dmft] index), restorative status (F/f + D × 100) and caries severity (using the visible pulpal involvement, ulceration as a result of displaced tooth fragments, fistula and abscess [PUFA/pufa] index) were carried out.Results:A total number of 391 children participated in the study; 58.8% were female and 41.2% were male with their mean age being 9.99 (±0.18) years. The DMFT for the study population was 1.71, while dmft was 1.81 and 51.4% of the participants had MIH; generally, the restorative index for the population was low (3.2). Children with MIH had a higher number of decayed teeth compared to children without MIH (P= 0.001); Overall, DMFT was higher in MIH-affected children. There was a significant difference in teeth with pulpal involvement (P= 0.01) and teeth with abscess formation (P= 0.02) in children with MIH compared to children without.Conclusion:Children with MIH had higher prevalence of caries and was more severe, compared to children without MIH.